2023
DOI: 10.3390/su151310341
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Influencing Factors on Consumer Behavior Using the AHP Model

Abstract: The influence of numerous factors determines and changes the daily behavior of consumers. This paper aims to estimate and rank the weight of cultural, social, personal, and psychological factors that change the buying habits of individuals. The research was conducted on a sample of 559 respondents in the Republic of Croatia. Data from the survey were used to create a hierarchical model structure. The analytic hierarchy process (AHP), as a decision-making method, was used in the analysis to estimate and rank th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…Similarly, consumers with a higher fondness for brands show a weakened relationship between promotional offers and perceived personal fit with the brand (Papadopoulou et al, 2023;Phau & Lau, 2000). These moderating effects highlight the importance of considering individual consumer characteristics when crafting advertising strategies incorporating promotional offers (Lemon & Verhoef, 2016;Alsharif et al, 2022;Šoštar & Ristanović, 2023).…”
Section: -Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, consumers with a higher fondness for brands show a weakened relationship between promotional offers and perceived personal fit with the brand (Papadopoulou et al, 2023;Phau & Lau, 2000). These moderating effects highlight the importance of considering individual consumer characteristics when crafting advertising strategies incorporating promotional offers (Lemon & Verhoef, 2016;Alsharif et al, 2022;Šoštar & Ristanović, 2023).…”
Section: -Discussionmentioning
confidence: 96%
“…The study's practical implications enable advertisers and marketers to make choices that will optimize the efficacy of promotional tactics, enhance consumer connection with brands, and propel company expansion in the cutthroat retail environment of today. Findings offer valuable guidance for strategic brand positioning, carefully designing promotional offers, segmentation and targeting, consumer engagement strategies, and the effectiveness of promotional offers in influencing brand perception and consumer behavior Alsharif et al, 2022;Šoštar & Ristanović, 2023).…”
Section: -Implications Of This Studymentioning
confidence: 99%
“…This factor is very important because good relationships with customers can help build deep trust and increase the level of customer loyalty. In addition, the social factor in CRM also includes a deep understanding of culture, social values and societal norms that influence customer behaviour [15]. Companies need to recognise the diverse cultures and backgrounds of their customers, and wisely integrate this understanding into their CRM strategies.…”
Section: Figure 1 Flowchart Methodologymentioning
confidence: 99%
“…It is suggested that comparative analyses and collective reviews of related studies may be conducted to provide generalizable findings. In relation to this, Sostar and Ristanovic [104] explained that geographical context may also influence generalizability. Therefore, sensitive data collection processes could be considered which are relevant to the geographical settings of future studies.…”
Section: Limitations and Recommendations For Future Researchmentioning
confidence: 99%